Credit Booms and Lending Standards : Evidence From the Subprime Mortgage Market - Dell'Ariccia, Giovanni (IMF Working Papers; Working Paper ;, 2008)
This paper links the current sub-prime mortgage crisis to a decline in lending standards associated with the rapid expansion of this market. We show that lending standards declined more in areas that experienced larger credit booms and house price increases. We also find that the underlying market structure mattered, with entry of new, large lenders triggering declines in lending standards by incumbent banks. Finally, lending standards declined more in areas with higher mortgage securitization rates. The results are consistent with theoretical predictions from recent financial accelerator models based on asymmetric information, and shed light on the relationship between credit booms and financial instability.